Genistein as a neuroprotective agent: a comprehensive review of its potential in neurodegenerative diseases: Review article (Journal of Pharma Insights and Research, 2023)
Neurodegenerative diseases (NDDs) are generally identified by the sudden decrease in neuronal disruption in normal and subsequent cell death in the brain or peripheral nervous system underlying conditions, such as Parkinson's disease, Alzheimer's disease, Huntington's disease, and amyotrophic lateral sclerosis, lack of effective treatments shown to slow down their progression. Natural compounds derived from plants have demonstrated potential efficacy in combating various diseases, including neurodegenerative disorders. This review article evaluates the molecular targets and therapeutic potential of isoflavones, with a particular focus on genistein, in the treatment of neurodegenerative diseases. Both in vivo and in vitro studies have indicated the neuroprotective effects against NDDs. We aim to provide a comprehensive overview of the role played by genistein in delaying the development, mechanisms of action and progression of neurodegenerative diseases. Additionally, we examine the current evidence supporting the use of genistein in preclinical and clinical studies, highlighting its potential therapeutic benefits in neurodegenerative disorders. However, further research is needed to elucidate optimal dosage, bioavailability, and long-term safety profiles, also to investigate potential synergistic effects with existing therapies. The insights provided in this review may contribute to the development of novel therapeutic strategies for the management of these devastating disorders.